In-situ x-ray diffraction study of y-Mg(BH4)2 decomposition - Paskevicius, Mark; Pitt, M.; Webb, C.; Sheppard, Drew; Filso, U.; Gray, E.; Buckley, Craig (American Chemical Society, 2012)
We have studied the complex decomposition mechanism of cubic γ-Mg(BH4)2 (Ia3̅d, a = 15.7858(1) Å) by in-situ synchrotron X-ray diffraction, temperature-programmed desorption, visual observation of the melt, and Fourier transform infrared (FTIR) spectroscopy. The decomposition and release of hydrogen proceeds through eight distinct steps, including twopolymorphic transitions before melting, with a new ε-Mg(BH4)2 phase at ca. 150 °C. After melting, strong changes in sample color from yellow to brown to gray are consistent with the unknown Mg−B−H phase(s) (that diffract with high d-spacing halos) in the sample changing from an average composition of MgB2H5.3 at 325 °C, to MgB2.9H3.2 at 350 °C, and to MgB4.0H3.7 by 450 °C. From 350 to 450 °C, the crystalline Mg proportion increases. No combination of previously assigned anionic BnHm species (including MgB12H12 and Mg(B3H8)2) can account for the average composition of the unknown proportion of the sample. This is supported by FTIR spectra showing an absence of terminal B−H resonances in the 2500 cm−1 region that are present for B12H12 and B3H8 anionic species. Our combined analysis strongly indicates the presence of as yet unidentified Mg−B−H phase(s) in postmelted decomposed Mg(BH4)2 samples.